ANALISIS PROGRAM CORPORATE SOCIAL MARKETING, PENGETAHUAN KONSUMEN DAN REPUTASI PERUSAHAAAN DALAM MENCIPTAKAN GREEN CONSUMERISM (PROGRAM TUMBLER STARBUCKS) - Akhmad Irwansyah (Universitas Batanghari Jambi, 2015)
The aim of this study is that consumers of Starbucks Coffee interested, conscious, want to move on and continue to use tumber Starbuck on the go in the activities of consumption as consumers are partly responsible for environmental sustainability. This study uses a quantitative approach (quantitative approach). Based on the results of data analysis and discussion before it can be concluded- the research findings as follows: 1. The program of corporate social marketing in the form of Starbucks Coffee Starbucks tumbler on the go affect the consumer's knowledge. It is stated that the program of social marketing as practiced by Starbucks Coffee can provide knowledge to the consumer to act in an environmentally friendly consumption 2. corporate social marketing program in the form of Starbucks Coffee Starbucks tumbler on the go affect the company's reputation. By fulfilling obligations as a company conducting its business in a responsible manner then it will be a positive influence on the company's reputation as a green company in the eyes of the public. 3. Knowledge of consumer influence on the consumer Consumerism green to consume drinks bought at Starbucks Coffee. When a consumer has been educated to do that consumption of green and know that such knowledge can directly affect the consumer in making the consumption of green or green behaves Consumerism. 4. The effect on the company's reputation in the consumer Consumerism green consume drinks bought at Starbucks Coffee. Currently, the company has established a reputation as a green company where the company's reputation is also considered good by the public, the public will be encouraged and influenced by the extension or invitation offered by corporate social marketing undertaken by the company happened the call so that consumers behave participate in green shows the continuity of the preservation of the earth. 5. The corporate social marketing program in the form of Starbucks Coffee Starbucks tumbler on the go affect the green Consumerism consumers Starbucks Coffee.Keywords: Analysis, Corporate Social Marketing, Consumer Sciences, on the Company's reputation, Green Consumerism.